Computer modeling of water distribution systems - Robinson, Laredo; Edwards, Jerry A.;Willnow, Lindle D. (Denver : American Water Works Association, 2012)
This manual provides distribution engineers and operators with information on developing and using computer hydraulic models of water distribution systems.
Introduction to distribution system modeling-- building and preparing model-- tests and measurements-- hydraulic calibration-- steady-state simulation-- extended-period simulation-- water quality modeling-- transient analysis-- storage tank mixing and water age
Includes bibliographical references.
Keywords: WATER -- DISTRIBUTION